Toward a broader approach to organization development - Kobrak, Peter (1993)
If organization development (OD) is to realize its full potential it needs a broader approach. Although in theory OD continues to be treated as an organizational ideal type and is posed as a dramatic departure from existing organizational forms, in practice, numerous public and private organizations are increasingly integrating a number of OD practices into their ongoing activities. This paper argues that we should devote less attention to OD as a full-fledged, alternative organizational form and more time examining the emerging literature that depicts how OD is being absorbed into a wide range of administrative arrangements. We should place more emphasis on learning how this purpose-driven change is occurring and on how both those external and internal environmental influences are leading to more subtle and more incremental shifts in organizational design and culture over time. Only in this fashion can OD gain the greater acceptance that it deserves. - Reproduced
Keywords: Organizational change; Organizations